Salmonellosis in the COVID19 Pandemic Era - A. V. Lubimova; N. V. Satosova; R. V. Kitsbabashvili (Эпидемиология и вакцинопрофилактика)
Relevance. In 2020, there was a unique situation caused by the COVID-19 pandemic and the anti-epidemic measures introduced in this regard. To date, the question of how these methods affect the spread of other infectious diseases, including salmonellosis, has not been studied.Target. To assess the impact of anti-epidemic measures during the COVID-19 pandemic on the epidemic process of salmonella infection in St. Petersburg.Materials and methods. Reporting form No. 2 of Rospotrebnadzor «Information on infectious and parasitic diseases» for 2018–2020 and data from the State report «On the state of sanitary and epidemiological well-being of the population in St. Petersburg in 2019», «On the state of sanitary and epidemiological well-being of the population in St. Petersburg in 2020». Data processing was carried out using Microsoft Excel (Microsoft®, USA), Statistica for Windows (StatSoft®, USA) with the determination of the level of significance (p), the calculation of confidence intervals (95% CI) was carried out in the EpiTools application.Results. The incidence of salmonellosis in 2020 was significantly lower than in the previous 2 years 28.86 (95% CI 27.45–30.34) per 100 ths population, and in 2019 and 2018 – 49.8 (95% CI 47.9–51.7) and 39.21 (95% CI 37.6– 40.9) per 100 ths of the population respectively. When analyzing the incidence of salmonellosis in 1995 to 2020, it was revealed that in 2020 the incidence rate was the lowest over the past 25 years and below the multi-year average (37 per 100 ths population) in St. Petersburg by 22%. A decrease in the incidence of salmonellosis was observed in 2020 and in the Russian Federation as a whole compared to 2019, the indicator increased 1.6 times and amounted to 14.71 per 100 ths rubles. population (multi-year average – 29.1). In 2020, there was a change in the intra-annual incidence of salmonellosis. While the peak incidence of salmonellosis persisted in the autumn period (September–October), in 2020 there was no characteristic rise in the spring period, as was observed in 2018 and 2019, which may be due to the spring lockdown (p = 0.03). The decrease in the incidence of salmonellosis was due to a significant decrease in the incidence among adults, while this was not observed in other age groups. In 2018–2020, diseases in the population were caused by 61 serotypes of Salmonella: in 2018 – 33, in 2019 – 32, and in 2020 – 39 serotypes. During the pandemic, the decrease in the incidence of salmonellosis was due to the decrease in the incidence caused by S. Enteritis, which in 2020 amounted to 19.91 (95% CI 18.73-21.14) per 100 thousand population, while in 2019 – 39, 01 (95% CI 37.4–40.7) and in 2018 – 31.24 (95% CI 29.8–32.8) per 100 ths population. At the same time, the decrease in the incidence rate was a decrease in the incidence rate among adults, while in other age groups no changes in the incidence rate were observed. The incidence due to other salmonella serotypes did not change. There were no significant differences in the incidence of salmonellosis by sex and age.Conclusion. The measures introduced during the pandemic in 2020 led to a decrease in the incidence of salmonellosis in St. Petersburg by reducing the incidence of salmonellosis caused by S. Enteritidis among adults.